THE EFFECTIVENESS OF HALAL CERTIFICATION ON CONSUMER TRUST AND LOYALTY OF INDONESIAN PHARMACEUTICAL PRODUCTS - Fatmawati, Reni; Siti Aisah; Anastasia Adinda Permata Putri; Revalina Dwi Alyani (IZZI: Jurnal Ekonomi Islam, 2025)
Halal certification has become an important aspect of the pharmaceutical industry in Indonesia, a country with a majority Muslim population. This study aims to explore how halal certification affects consumer trust and loyalty towards pharmaceutical products in Indonesia. Through a comprehensive analysis, it is found that halal certification issued by the Indonesian Ulema Council (MUI) through the Halal Product Guarantee Organisation (BPJPH) has increased the trust and loyalty of Muslim consumers. Halal certification provides a guarantee of product safety and hygiene, thereby increasing consumer satisfaction and loyalty. A comparison with halal certification practices in other countries, such as Malaysia and Saudi Arabia, also provides insight into the differences and similarities in the regulatory framework and certification process. Recommendations include improving the halal certification process, increasing awareness and education, harmonising halal certification standards, and utilising technology and digitalisation.